Impact of Corporate Sustainability on Firm Value: Indonesian Context - Muhammad Yusuf Shalihin; Harry Suharman; Dede Abdul Hasyir (Universitas Padjadjaran, 2020)
Sustainability reports emerge as a critical problem in the business world. Companies do not merely pursue profit maximization, but must pay attention to non-financial factors to maintain long-term growth. This study aims to investigate the relationship between company sustainability and company value. This study involved a sample of companies included in the proper index listed on the capital market and included in the category of 45 of the most actively traded companies (LQ45) on the Indonesia Stock Exchange with a study period of 2015-2018. Sample selection by purposive sampling method with the final results obtained 20 sample companies that meet the sample criteria. Then the data is tested with the Generalized Method of Moment (GMM) estimation model analysis method. The results of this study indicate that corporate sustainability has a positive effect on the value of market-based companies. This research implies that companies and the Indonesian government must pay attention to increasing sustainability reporting. Because it is proven to be used as a corporate strategy in improving long term performance and maximizing company value.